The Influence of Audit Fees, Audit Tenure, and Auditor Switching on Audit Quality - Zaafaranie, Sahnon Dhabit; Wati, Nisa Nila; Angga, Angga; Rosnidah, Ida (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2024)
Financial statement falsification involving company management and auditors is a prevalent issue in the business landscape. Ensuring the integrity of audit outcomes holds paramount importance in verifying the adherence of financial statements to generally accepted accounting standards (GAAP). Consequently, auditors are expected to maintain high professionalism, prioritizing objectivity over personal considerations in executing their responsibilities. This research aimed to assess the impact of audit fees, audit tenure, and auditor turnover on audit quality. Employing a quantitative research methodology, descriptive analysis and logistic regression tests were conducted to evaluate the hypotheses. The study targeted publicly traded companies within the financial sector, specifically in the insurance sub-sector, listed on the Indonesia Stock Exchange (IDX) from 2018 to 2022. Sample selection utilized purposive sampling techniques. Results reveal that audit fees significantly influence audit quality, whereas audit tenure and auditor turnover do not exhibit significant effects. This study contributes to efforts aimed at advancing audit quality.